Significant reduction in red blood cell transfusions in a general hospital after successful implementation of a restrictive transfusion policy supported by prospective computerized order auditing. Issue 10 (27th March 2014) - Yerrabothala, Swaroopa; Desrosiers, Kevin P.; Szczepiorkowski, Zbigniew M.; Dunbar, Nancy M.
Abstract : Background: Our hospital transfusion policy was recently revised to recommend single‐unit red blood cell transfusion (RBC TXN) for nonbleeding inpatients when the hemoglobin (Hb) level is not more than 7 g/dL. Our computerized provider order entry system was reconfigured to provide real‐time decision support using prospective computerized order auditing based on the most recent Hb level and to remove the single‐click ordering option for 2‐unit RBC TXNs to enhance compliance. This study was undertaken to assess the impact of these changes on hospital transfusion practice. Study Design and Methods: This study analyzed the total number of transfusion events, proportion of single and 2‐unit transfusions and the Hb transfusion trigger in the preimplementation period (October 2011‐March 2012) compared to the postimplementation period (October 2012‐March 2013). Results: In the postimplementation period the total number of RBC units transfused/1000 patient‐days decreased from 60.8 to 44.2 (p < 0.0001). The proportion of 2‐unit TXNs decreased from 47% to 15% (p < 0.0001). We also observed significant decreases in pretransfusion Hb triggers. Conclusion: Implementation of restrictive transfusion policy supported by prospective computerized order auditing has resulted in significantly decreased RBC utilization at our institution.